2023
DOI: 10.1007/s13280-023-01852-1
|View full text |Cite|
|
Sign up to set email alerts
|

Meeting the challenges of wild boar hunting in a modern society: The case of France

Abstract: Modern hunting is an ambivalent practice, torn between leisure and labor. Nowhere are these conflicting dimensions better manifested than for wild boar—a simultaneous game and pest species in many countries. Here, we consider the sociological, political and cultural phenomenon of wild boar hunting from a change perspective, starting at its historical roots to future implications concerning the changing demographics, drivers, needs and practices of a modernizing hunting community. Using the case context of Fran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 93 publications
0
0
0
Order By: Relevance
“…Management of wild boar has recently focused on facilitating high hunting pressure to regulate population size (e.g. Apollonio Vajas et al 2023) reported that hunting is the main cause of wild boar mortality and therefore a feasible way to modulate its population dynamics (see also Quirós-Fernández et al 2017). In this context, some authors raise that more knowledge on various aspects of wild boar ecology and hunting dynamics are needed to develop effective population control strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Management of wild boar has recently focused on facilitating high hunting pressure to regulate population size (e.g. Apollonio Vajas et al 2023) reported that hunting is the main cause of wild boar mortality and therefore a feasible way to modulate its population dynamics (see also Quirós-Fernández et al 2017). In this context, some authors raise that more knowledge on various aspects of wild boar ecology and hunting dynamics are needed to develop effective population control strategies.…”
Section: Introductionmentioning
confidence: 99%